The process zone around the tip of cracks in metal matrix composites - Kourkoulis, S.K. (Archives of Mechanics, 2003)
Some characteristics of the process zone developed around the tips of cracks as well as the fractography of the fracture surfaces constitute the subject of the present paper. The study was carried out using Scanning Electron Microscopy for the determination of the Crack Tip Opening Displacement, while numerical analysis and experimental results were combined for the determination of the J-integral. A modern particulate Metal Matrix Composite and its matrix alloy were used for the fabrication of relatively thin tensile specimens of two different types, i.e. single- and double-edge-notched. Dependence of the above quantities on the thickness of the specimen is detected: both the critical Crack Tip Opening Displacement and the critical J-integral are found to increase in an almost linear manner with thickness. For comparison, intact prismatic specimens were considered, in order to study the dependence of ductility and fracture on the thickness of the specimen. It is observed that they depend also on the specimen thickness in a similar manner. Variation of these two properties with the direction of the specimen with respect to the rolling axis is also detected, indicating the importance of the plastically induced anisotropy due to the manufacturing process. Concerning the mechanisms leading to failure, it is concluded that void coalescence is active although void nucleation due to the presence of particles appears to be unavoidable.